Improvements in HCV-related Knowledge Among Substance Users on Opioid Agonist Therapy After an Educational Intervention. Issue 2 (March 2016) - Zeremski, Marija; Zavala, Roberto; Dimova, Rositsa B.; Chen, Yang; Kritz, Steven; Sylvester, Clewert; Brown, Lawrence S.; Talal, Andrew H.
Abstract : Supplemental Digital Content is available in the text Abstract : Objectives: Lack of knowledge about hepatitis C virus (HCV) is a principal barrier to substance users' engagement into care for the infection. As a step toward their increased engagement into HCV care, the objective of this study was to deliver an HCV-related educational intervention to substance users on opioid agonist therapy and to assess the change in HCV-related knowledge after the intervention. Methods: We designed a comprehensive and interactive hepatitis C-related educational intervention, composed of two 30 to 60-minute sessions conducted during 2 consecutive weeks. Patients' knowledge about hepatitis C was assessed immediately before and after the intervention using a 7-item questionnaire. Results: A total of 110 patients completed both educational sessions. Patients' mean age was 54.7 ± 7.8 years, 58.7% were men, 70.4% African American, and 30% were Hispanic. We observed a significant increase in HCV-related knowledge after completion of the educational intervention. Whereas 65.45% of patients answered 5 or more questions correctly before the intervention, 83.64% had 5 or more questions answered correctly on the posteducational quiz ( P < 0.001). Male sex, ever receiving an HCV diagnostic test before the educational intervention, and a higher level of HCV knowledge on the preeducational quiz were found to be significantly associated with HCV-related knowledge after the educational intervention. Conclusions: Patients' knowledge about hepatitis C was found to be significantly improved after the educational intervention. Therefore, HCV-related education could be the first step toward effective enrollment of patients on opioid agonist therapy into hepatitis C care.